A study based on functional near-infrared spectroscopy: Cortical responses to music interventions in patients with myofascial pain syndrome - Zhang, Jiayue; Shi, Ping; Du, Jiahao; Yu, Hongliu (Frontiers in Human Neuroscience, 2023)
Object: This study measured cerebral blood oxygen changes in patients with myofascial pain syndrome (MPS) using functional near-infrared spectroscopy (fNIRS). The aim was to investigate the effect of music intervention on pain relief in MPS patients. Materials and methods: 15 patients with MPS participated in this study. A self-controlled block task design was used to collect the oxy-hemoglobin ([HbO2]) and deoxy-hemoglobin ([HbR]) concentrations in the prefrontal cortex (PFC) and motor cortex using fNIRS. The cerebral cortex response and channel connectivity were further analyzed. In the experiment, the therapist was asked to apply compression of 3-4 kg/cm2 vertically using the thumb to induce pain. Soothing synthetic music with frequencies of 8-150 Hz and 50-70 dB was used as the audio for the music intervention. Result: Compared to the group without music intervention, the activation of brain regions showed a decreasing trend in the group with music intervention under the onset of pain. The results of paired t-tests showed that nine of the data were significantly different (p<0.05). It was also found that with music intervention, inter-channel connectivity was diminished. Besides, their dorsolateral prefrontal cortex (dlPFC) was significantly correlated with the anterior prefrontal cortex (aPFC) for pain response (r=0.82), and weakly correlated with the premotor cortex (r=0.40). Conclusion: This study combines objective assessment indicators and subjective scale assessments to demonstrate that appropriate music interventions can be effective in helping to relieve pain to some extent. The analgesic mechanisms between relevant brain regions under music intervention were explored in depth. New insights into effective analgesic methods and quantitative assessment of pain conditions are presented.